Título de la tesis: Representación de los colectivos GLBTI en el periodismo de información de Diario Los Andes, período 2022. - Vivas Vera, Mirsa Leonela (2024)
ABSTRACT: The representation of LGBTQ+ collectives in the media, such as the newspaper Los Andes, is a crucial issue in Riobamba and Ecuador, where stereotypes and discrimination persist. This qualitative study analyzes Los Andes' coverage during 2022, finding limited visibility of LGBTQ+ topics, with only 4 news items among 48 publications. This lack of representation restricts the dissemination of information about the challenges and achievements of the LGBTQ+ community, which can negatively impact the fight for equality. The media plays a significant role in shaping opinions and social attitudes, hence a more equitable and diverse coverage is recommended. The exclusion of LGBTQ+ topics can perpetuate stigmas and prejudices, and Los Andes' conservative bias may contribute to the marginalization of the community. It is suggested to allocate resources to LGBTQ+ coverage, train staff, and promote an inclusive editorial policy to enhance representation and promote equality in the media. Keywords: representation, media, LGBTQ+, discrimination, inclusion.